Fruitful or unfruitful: strawberry and tomato specific immunoglobulin E testing at a tertiary pediatric center - Chong, Albert C.; Izadi, Neema; Chwa, Won Jong; Tam, Jonathan S. (Frontiers in Allergy, 2023)
Background Suspected strawberry and tomato (S/T) food allergy (FA) may be evaluated using specific immunoglobulin E (sIgE) testing despite its low specificity and positive predictive value. Objective To understand ordering patterns for S/T sIgE testing and identify relevant factors to clinical decision-making. Methods We retrospectively reviewed 814 patients with sIgE testing available for strawberry (651), tomato (276), or both (113) from January 2012 to May 2022 at a tertiary pediatric hospital. Patient demographics, provider specialty, and reasons to test were collected. Student’s t-test and multiple regression analyses were used to test the association between S/T sIgE levels and clinically relevant outcome (CRO) status. Fisher’s exact test and general linear models were used to evaluate and compare potential predictive factors for CRO status. Results Allergy and immunology, gastroenterology, and general pediatrics ordered most S/T sIgE testing. Testing was ordered most frequently for non-IgE-mediated GI symptoms, mild possible IgE-mediated reactions, and eczema, and in infants and school-age children. Mean sIgE levels were higher for cases resulting in a CRO when controlling for other predictor variables (p = 0.015; p = 0.002 for S/T, respectively). Only 2.2% and 5.4% of tests resulted in a CRO for S/T and severe allergy was rare. Testing for non-IgE-mediated GI symptoms or eczema, or in non-atopic patients, yielded no CROs. Exposure and reaction history of present illness (ERH) was associated with CROs (p < 0.001; p = 0.04) with a high negative predictive value (99.5%; 100%) and low positive predictive value (11.5%; 15.0%). ERH (p < 0.001, η2 = 0.073; p = 0.009, η2 = 0.123) was a more significant predictor than sIgE levels (p = 0.002, η2 = 0.037; p = 0.212, η2 = 0.030) for CRO status. Conclusion The diagnosis of S/T food allergy is made primarily based on clinical history. S/T sIgE testing for children and adolescents should be avoided for patients without an ERH and in the workup of non-IgE-mediated GI symptoms. Testing for eczema and non-atopic patients is likely low-yield.